MORSICATIO BUCCARUM AND LABIORUM IN SEVERE ANXIETY PATIENT - Dewi Sulaksana, Sutrania; Reni Yuslianti, Euis (Journal of Health and Dental Sciences, 2024)
Morsicatio buccarum and labiorum are conditions generally caused by chronic habitual cheek and lip biting. Objective findings present thick, shaggy, irregular white lesions on the buccal and labial mucosa. Morsicatio is frequently associated with psychological conditions. This case report aims to assess the depression, anxiety, and stress levels in a patient with morsicatio buccarum and labiorum. A 22-year-old male patient visited the Integrated Polyclinic of Universitas Jenderal Achmad Yani Dental Hospital to check his oral status. Clinical examination revealed incidental findings. Extraoral examination showed clicking on both temporomandibular joint (TMJ) and lip desquamation sides. Intraoral mucosa examination revealed white lesions in the form of unsweepable plaque, irregular, slightly elevated from surrounding tissue, and interspersed with erythematous erosion areas on the buccal and labial mucosa. A pigmented lesion was found on the anterior attached gingiva mucosa on both the upper and lower jaws. The patient admitted to chronic habitual cheek biting since childhood. The Depression, Anxiety, and Stress-21 (DASS-21) assessment showed anxiety reaching a severe level. A psychological approach is needed as part of the treatment planning in morsicatio cases. DOI : 10.54052/jhds.v4n2.p147-156